Effect of Sulfur-Containing Primers for Noble Metals on the Bond Strength of Self-Cured Acrylic Resin - Keiichi Yoshida (MDPI AG, 2017)
This study investigated the effect of sulfur-containing primers for noble metals on the shear bond strength of self-cured acrylic resin after thermal cycling (TC). Four pure metals (Au, Ag, Cu, and Pd) and type IV Au alloy were either untreated, or treated with one of the five sulfur-containing metal primers (V-Primer, Metaltite, Alloy Primer, Metal Link Primer, and Metal Primer Z). Afterwards, a brass ring was placed on the metal surface and filled with self-cured acrylic resin (n = 10). The bond strengths were measured after 24 h (TC0) and after 2000 thermal cycles at 4-60 °C (TC2000). Three-way ANOVA and Tukey compromise post hoc tests were used to analyze the data (α = 0.05). All of the sulfur-containing primers significantly improved the resin bond strength as compared to that of the non-primed group at TC0 regardless of the metal type (p < 0.05). However, at TC2000, the bond strengths between the resin and the five metals significantly decreased with respect to the values obtained at TC0 regardless of the primer (p < 0.05). The sulfur-containing metal primers, except for Metal Link Primer, were found to be more effective for improving the bond strength between the self-cured acrylic resin and Ag as compared to the other three pure metals (p < 0.05). The bond strengths between the resin and Au and type IV Au alloy at TC2000 were the highest ones when Metal Primer Z was used.